Detailing for acoustics / Peter Lord and Duncan Templeton - Lord, Peter (E & FN Spon, 1996)
This unique manual provides a comprehensive set of constructional details, drawn to scale and showing how the best results can be achieved by correct detailing. The details are arranged for ease of use under headings of Objectives, Sound Insulation, Sound Absorption/Reflection, Services, Definitions and Tables. This revised and updated edition of a well-established manual includes considerable improvements for easier and more accessible use of the information: detail sheets have been rearranged under new headings, graphics have been improved and acoustic performance data expanded. The authors also give advice on the appropriate materials and assemblies. Architects, acousticians, students, structural and services engineers and interior designers will find this comprehensive design guide an invaluable reference source and drawing board aid.